Rural youth in Mexico. A review based on population censuses - Fuentes, Elena (2025)
To show the situation of rural youth in Mexico, a study of their main activities was carried out using information from the Population Censuses of 2000, 2010, and 2020. The analysis was conducted by gender and three age groups: 15 to 19, 20 to 24, and 25 to 29 years. The results showed that young people in the first group tend to focus on studying; as they get older, family trajectories are established, such as the formation of nuclear families, particularly in common law, and career trajectories. Men especially enter the labor market in construction activities and agriculture, where salaries are lower and higher education is not required. Meanwhile, women remain in school for a very short time, with a smaller proportion moving into the labor market in non-agricultural sectors and a larger proportion devoting themselves to domestic chores.